Observational indications of downward-propagating gravity waves in middle atmosphere lidar data. (September 2017) - Kaifler, N.; Kaifler, B.; Ehard, B.; Gisinger, S.; Dörnbrack, A.; Rapp, M.; Kivi, R.; Kozlovsky, A.; Lester, M.; Liley, B.
Abstract: Two Rayleigh lidars were employed at a southern-hemisphere mid-latitude site in New Zealand (45°S) and a northern-hemisphere high-latitude site in Finland (67°N) in order to observe gravity waves between 30 and 85 km altitude under wintertime conditions. Two-dimensional wavelet analysis is used to analyze temperature perturbations caused by gravity waves and to determine their vertical wavelengths and phase progression. In both datasets, upward phase progression waves occur frequently between 30 and 85 km altitude. Six cases of large-amplitude wave packets are selected which exhibit upward phase progression in the stratosphere and/or mesosphere. We argue that these wave packets propagate downward and we discuss possible wave generation mechanisms. Spectral analysis reveals that superpositions of two or three wave packets are common. Furthermore, their characteristics often match those of upward-propagating waves which are observed at the same time or earlier. In the dataset means, the contribution of upward phase progression waves to the potential energy density E p is largest in the lower stratosphere above Finland. There, E p of upward and downward phase progression waves is comparable. At 85 km one third of the potential energy carried by propagating waves is attributed to upward phase progression waves. In some cases E p of upward phase progression waves far exceeds E p of downward phase progression waves. The downward-propagating waves might be generated in situ in the middle atmosphere or arise from reflection of upward-propagating waves. Abstract : Highlights: Downward propagating gravity waves occur frequently above New Zealand and Finland. At 85 km altitude, downward propagating waves carry one third of the potential energy. Spectral properties of upward and downward propagating waves are often comparable.